Strategies for Treating Acute Migraines and Identifying Triggers. Literature review - Kotowicz, Zuzanna; Pabiś, Jakub; Podgórski, Piotr; Górecka, Sandra; Olszański, Miłosz; Bogusz, Aleksander; Kwiatkowski, Oskar; Kołodziej, Anna; Król, Anita (Journal of Education, Health and Sport, 2024)
Introduction Migraine, a prevalent neurological disorder affecting a substantial portion of the global population, poses a significant burden on individuals' overall quality of life. While the exact pathophysiological mechanisms underlying migraine headache attacks remain elusive, the involvement of trigeminal pathway activation is well-documented. A multitude of factors, collectively termed triggers, have been identified as capable of precipitating migraine episodes, ranging from dietary components to environmental stimuli such as bright lights and weather fluctuations. Migraine headaches typically manifest as throbbing pain localized predominantly on one side of the head and are often accompanied by a constellation of additional symptoms including photophobia, phonophobia, and nausea. The management of migraine involves a diverse array of therapeutic modalities tailored to the specific characteristics of the pain experienced. These may include the administration of non-steroidal anti-inflammatory drugs (NSAIDs), paracetamol, triptans, and antiemetics, among others. This study endeavors to explore the most prevalent triggers implicated in migraine onset, as well as contemporary treatment strategies, with an emphasis on incorporating the latest research findings and therapeutic advancements in this evolving field. Aim of the study This review aims to identify symptoms, triggers of acute migraine and solutions in its treatment process, including latest developments. Material and method This article presents the current state of knowledge about acute migraine, triggers and treatment options in various scientific articles. Publications describing acute migraine attacks and treatments including the most recent reports in the field were reviewed using the PubMed platform. The search included the keywords ‘migraine, 'migraine triggers', 'triptans', 'migraine with aura'.